His Majesty King George V. Death of I (Colonial Letters and the Contact of Knowledges, 1936)
This file contains colonial letters on the death of George V.
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies